DETERMINASI FAKTOR SOSIAL-EKONOMI TERHADAP FASILITAS PENDIDIKAN MENGGUNAKAN PEMODELAN LOGISTIK ORDINAL DI DESA TUNTUNGAN: Determination Of Socio-Economic Factors On Educational Facilities Using Ordinal Logistic Mideling In Tuntungan Village - Maulana, Putri Jehan; Luthfiyah, Farica; Citra, Indah Tribuana; Siregar, Anisa Hafizah (Al-Aqlu: Jurnal Matematika, Teknik dan Sains, 2025)
The purpose of this study was to use an ordinal logistic regression model to analyze socioeconomic factors in children's educational institutions in Tuntungan village. This study collected primary data on family economic status (high, medium and low categories) and social environment (very supportive, supportive, less supportive and non-supportive categories) from 100 respondents. The results of the analysis show that families' economic status significantly affects the quality of education facilities for their children, with families with higher economic status having better access compared to families with medium and low economic status. In addition, although not as large as economic position, socio-ecological status is also important. The resulting logit model shows that economic variables have a greater influence on the quality of children's educational institutions compared to social variables. This study emphasizes the importance of improving the local economy to expand access to high-quality education